E-passport security using advanced encryption standard (AES) - Mohd Taujuddin, Nik Shahidah Afifi (2007)
This paper presents basic design approach for securing the information in the E-passport by using Advanced Encryption Standard (AES) algorithm. AES is a new cryptographic algorithm that can be used to protect electronic data. Furthermore, AES is an iterative; symmetric-key block ciphers that can use keys of 128, 192, and 256 bits, and encrypt and decrypt data in blocks of 128 bits (16 bytes). An algorithm successfully implemented using Visual Basic. The purpose of AES algorithm is to protect the information stored in Epassport. E-passport is the new version of the conventional passport that usually contain the holder's profiles such as photograph, signature, date of birth, nationality, and sometimes other means of individual identification. The E-passport is very similar to the previous passport, but the different only having an embedded microchip in the centre page but for this prototype, microchip will be replaced with the memory stick.